George Desvallières et la Grande Guerre - Catherine Ambroselli de Bayser (Revue LISA)
George Desvallières (1861-1950) took part in the 1914-18 War as battalion commander with the “Bataillon Des Vosges”, and depicted its tragic history on his return from the front. From 1883, he became a fully recognised artist with his painting being presented at all major Paris exhibitions. Founder, Vice-President, then President of the “Salon d’Automne”, he became known as a discoverer of young talents, and obtained recognition for both cubists and fauvists. At the start of the First World War, Desvallières joined up as a volunteer. Very quickly his men acknowledged him to be an unsurpassed leader, and demanded of his superiors that he be kept in his post, which was at first only a temporary appointment. Desvallières led his “chasseurs” across the Alsatian mountains for four years with determination, courage and a kindness recognised by all on the front. In March 1915, his seventeen-year- old son Daniel was killed in action a few miles away from his father. This loss affected him deeply, but thanks to his convert’s faith, he was able to sublimate this terrible ordeal. All his post-war work is centred on the theme of the soldier’s sacrifice for his country, which he assimilates to the sacrifice of Christ on the Cross. Some of his canvases are directly related to the War and to his son’s death, and his impressive wall-paintings on a similar theme made a profound impact on contemporary public opinion. The “Drapeau du Sacré-Coeur” (Banner of the Sacred Heart) at the Church of Notre Dame de Verneuil (1919) was the starting point for these murals. There followed such monumental works of pictorial expression as the Saint Privat Chapel in the Gard region (1920-1925), which will be discussed in this paper, the stained-glass windows at the Douaumont Ossuary (1927), the decoration of Wittenheim Church in Alsace (1929-1931), the Chapel of the Cité Saint Yves (1931) and the Way of the Cross at the Holy Spirit Church (1935) in Paris.* “George” without the “s” because of his Scottish ancestry.